Subjective evaluation of the environmental quality in China’s industrial corridors - Xu, Jian; Zhang, Mei; Shao, Long; Kang, Jian (Journal of Environmental Engineering and Landscape Management, 2016)
Based on 270 questionnaire surveys in 8 cities of 5 industrial corridors in China, this study aims to examine the effects of industry construction on the evaluation of environmental pollution, natural environment, built environment, personal perception and development and policy. The results show that the evaluations on environmental pollution and landscape design are both below the medium level, but the evaluations of the living comfort and safety are both above the medium level. Further analysis, females usually give lower evaluation scores than males, and age and health situations are negatively related to the evaluation results; People indicate a great desire to reduce the environmental pollution and protect the natural environment. Moreover, the landscape was analysed using colour extraction techniques based on video recording, there are significant correlations between industrial pixel ratio and evaluation results of air quality, vegetation pixel ratio and evaluation results of river water quality, and public facilities pixel ratio and evaluation results of comfort levels.